Phytopathogenic micromycetes of the town of Kalinkovichi - Lemeza, Nikolai A.; Hirilovich, Ivan S.; Dasko, Janina S. (Experimental Biology and Biotechnology, 2020)
As a result of the conducted researches in the territory of Kalinkovichi it was found 186 species of phytopathogenic fungi and fungus-like organisms, belonging to 4 divisions – Oomycota, Ascomycota, Basidiomycota and Deuteromycota. The detected micromycetes were parasitizing on 165 species of feeding plants from 45 families. The division of Ascomycota in the town of Kalinkovichi is represented by 70 species of 19 genera, the division of Basidiomycota – 32 species from 9 ge nera, the division of Deuteromycota – 47 species from 18 genera and the division of Oomycota – 37 species from 7 genera.
Keywords: micromycetes; oomycetes; ascomycetes; basidiomycetes; deuteromycetes; powdery mildew fungi; rust fungi